Mabarazanji as a Mirror of Gender Relations in Multicultural Education of the Bugis Bone Community - Syam, Syahrianti; Rosniar, Rosniar; Wandi, Wandi; Ridha, Arif; Bahtiar, Bahtiar (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to analyze how the practice of Mabarazanji in the Bugis Bone community reflects the division of gender roles influenced by local social and cultural constructions and examines it from an educational perspective. The research method used is a qualitative approach with the analysis of literature studies related to the practice of Mabarazanji, as well as the application of Talcott Parsons' social role theory to understand the social structure that affects gender roles in the practice. The results of the study showed that men in the practice of Mabarazanji often led and were directly involved in rituals as instrumental roles, while women were more often in supporting positions with logistical tasks as expressive roles. This reflects the division of gender roles that has been deeply rooted in the culture of the Bugis Bone community and serves to maintain stability and continuity of tradition. The conclusion of this study is that the practice of Mabarazanji not only functions as a religious ritual, but also serves as a means of reproduction of social values and the formation of individual identities based on gender roles in accordance with societal norms in the perspective of Islamic education, this is relevant because it shows how traditional and religious values can be combined in an effort to build individual character in accordance with the social and cultural goals of society. The educational implications of these findings show that education in the Bugis Bone community does not only focus on religious knowledge, but also on instilling social values that direct gender roles. However, this study also emphasizes the need for educational adaptation to achieve gender equality without sacrificing the integrity of local culture.